(untitled) (Journal of Social Sciences Review, 2023)
The eco-literacy study is relatively recent. E-literacy is the capacity to analyze an ecosystem and take action to preserve or restore it. This method might aid in bottom-up change. Eco literacy aids in the resolution of eco-challenges. Teaching, reading aloud to children, and using fashion as a platform may assist individuals in comprehending eco-concerns. The study is carried out to examine the role of public sector college libraries in eco-literacy; to identify the demographic factors related to eco-literacy and to assess college teachers’ and librarians’ perception of public sector college libraries’ participation in eco-literacy. The current study is descriptive in nature and Cross tabulation chi squares are used to obtain a representative cross-section of the population’s views and sentiments on a current issue through a survey. The participants of the study were the academics and librarians of the colleges in Bahawalpur District. Participants in the study also had a more positive perception of libraries’ role in fostering a more sustainable society and were likelier to say they would attend sustainability events hosted by a library. The current study led to the need for more empirical research on sustainable libraries and how the public sees libraries’ efforts to promote eco-responsibility. However, more research is required to fill a gap in the existing empirical literature.